High Coercivity in MnAl Disc Prepared by Severe Plastic Deformation. Issue 3 (5th March 2020) - Si, Ping Zhan; Lim, Jung Tae; Park, Jihoon; Lee, Hak Hyeon; Ge, Hongliang; Lee, Hyunjong; Han, Sangho; Kim, Hyoung Seop; Choi, Chul Jin
Abstract : Ping‐Zhan Si et al. (article number 1900356 ) have prepared bulk MnAl nanocrystalline alloy with a highest room‐temperature coercivity up to 0.59 T by using a high‐pressure torsion process. The severe plastic deformation process decreased the grain size of τ‐phase MnAl significantly. As a result, the coercivity of the MnAl was enhanced remarkably. This work opens a window for the development of bulk MnAl with high coercivity and enhanced remanence for applications of MnAl‐based magnets. – The cover article is part of the Special Section "Advanced Magnetic Oxides", comprising one Feature Article and 8 Original Papers (see the Preface, article number 2000058 ).